Exploring nightlife. Space, society and governance. - (:unkn) unknown (Rowman & Littlefield, 2018)
While the night has long been associated with crime and fear, over recent decades 'nightlife' has become increasingly associated with the creative economy, tourism, sociability, job growth, and urban regeneration. Debates about anti-social behaviour, morality, and safety continue to shape our understanding of the night but newer concerns have also emerged about gentrification, economic and social exclusion, commercialisation, and over-development. Comprising original contemporary research, the collection brings together case studies from across the globe that explore topics including nightlife and urban development, race, gender and youth culture, alcohol and drug use, and urban renewal. In doing so, each chapter explores nightlife in relation to local and global structures of power and governance. Exploring Nightlife is an ideal introduction to the emerging field of night-time studies and will be a valuable resource for students and researchers with an interest in geography, cultural studies, sociology, youth, leisure, and urban studies.
Keywords: Stadtsoziologie; Stadtentwicklung; Kommunalpolitik; Freizeitverhalten; Revitalisierung; Fallstudie; Nachtleben; Gentrifizierung; Governance; Gender mainstreaming; Raumnutzung; Städtetourismus; Jugendkultur